Seeking God’s Will: The Experience of Information Seeking by Leaders of a Church in Transition - Michels, David H. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
I explored the perspectives of leaders of churches in transition seeking to answer the question "what is God’s will for our church?" This is significant because religious information seeking has received little attention. Issues arising were feelings of frustration, the impact of digital media, and the role of prayer. J'ai exploré le point de vue des dirigeants religieux d'églises en transition cherchant à répondre à la question : « Quelle est la volonté de Dieu pour notre église? ». Cette étude est importante, car la recherche d'information en contexte religieux n'a reçu que très peu d'attention. Les enjeux observés comprennent le sentiment de frustration, l'impact des médias numériques et le rôle de la prière.